Association of Breastfeeding with Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis in mothers: A cross sectional survey - Muhammad Zafar Majeed Babar; Ghulam Mustafa; Manzur Ahmad Manzur; Hafiz Haseeb Ahsan (Journal of Aziz Fatimah Medical and Dental College)
Objective: To determine the association of Breastfeeding with Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis in mothers. Methodology: A cross sectional study on randomly selected 280 mothers presented in the outpatient department of Sheikh Zayed Hospital, Rahim Yar Khan for different medical reasons from July to Dec 2023. Data collection commenced after taking ethical approval from the Institutional Review Board of the institute and taking informed verbal consent from study subjects. These mothers were divided into 2 groups. Group 1 which never breastfed their children and group 2 which breastfed their children for more than 6 months. Each group had 140 participants. Subject having history of alcohol consumption or used medicines like glucocorticoids, amiodarone, tamoxifen, and methotrexate were excluded from the study. Biodata of all the participants along with demographic profiles were obtained, who then went through an LFT and Lipid profile blood sampling and an USG abdomen. Results were recorded on a predesigned proforma. Serum ALT, AST, Serum bilirubin, serum LDL, HDL, Triglycerides, and Serum Cholesterol were determined by enzymatic assay and high-performance liquid chromatography methods. Data was analysed using SPSS v.26. Descriptive statistics was used to summarize the data. Mean and standard deviations were reported for continuous variables. Chi square test was used to compare the qualitative variables, with p value of less than 0.05 taken as significant. Results: Mean age ± SD of participants was 40±4 years, with group-1 having mean age of 38.1±5 years and group-2 having 40.4±3 years (p=0.4). The findings showed that frequency of NASH in patients who have not breastfed their children was higher 19 out of 140(13.6%) whereas the mothers who breastfed their children only have 5% frequency of NASH i.e. 7 out of 140 (P value = 0.01). Out of 140 patients who did not breastfeed their children 56 (40.0%) developed NAFLD, contrary to 140 patients who breastfed their children only 20 (14.3%) (P value = 0.00) got NAFLD. Elevated ALT and AST levels are significant for NAFLD and NASH. Lipid profile is a major indicator of NAFL and NASH. Conclusion: The frequency of NAFLD and NASH is significantly low in mothers who breastfed their children. The frequency further decreases if the period of breastfeeding was greater.